Studies on Seasonal Occurrence, Incidence and Population Fluctuation of Shisham Leaf Binder, Dichomeris eridantis Mey - Ali, M.S.; Azam, F.; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
A systematic study was conducted on the seasonal sequence of occurrence, incidence and population fluctuation of Dalbergia sissoo leaf binder, Dichomeris eridantis Mey. in 1993. It revealed that moderate to maximum occurrence of the pest was recorded from February to October. Periodic incidence of the pest ranged from 0.30 to 10.80 in different growth stages of tree. The population of D. eridantis in different growth stages of tree varied from 9.99 to 18.00 and was recorded maximum in the 3rd week of June 1993. The maximum temperature showed significant and positive correlation (r = 0.912) with the population. Relative humidity had no significant effect. Â